Carol W. Brown - unknown:::Creator::::::::::::
Carol W. Brown sculpting the second bust of Steinbeck after the first was stolen in 1991. Unknown man on left. Ms. Brown had done the original in 1972. She was a former sister-in-law and classmate of Elaine Steinbeck.